Konstruksi Teologis dalam Hadih Maja - Lukman Hakim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Hadih Maja is an oral literature is the source of value in the lives of the  people of Aceh. The content itself hadih maja has a diverse range of values such  as the value of law, education, philosophy, ethics and theology. Lately hadih maja is oriented in the realm of law and social issues alone. It makes some of the  content of the hadih maja as neglected as the theological side. This paper  examines some of the central issues in the study of such concepts qadha kalam  and Qadar, rational reasoning and work ethic. In problem qadha and levels found  construction theological built in Acehnese society is the existence of an  understanding of kalam very balanced between the recognition of the absoluteness  of God and human freedom in realizing his actions. In the field of rational  reasoning, always taught the use of the maximum reasonable minds before doing  an action. Intellect is positioned as a tool to be able to measure the goodness and  badness of a deed. While the work ethic has always taught about the spirit and  optimism in life. This is the picture that proclaimed theological learning in hadih  maja. This of course is a decent value in the lives of the Acehnese appreciated